A Painlevé II model in two-ion electrodiffusion with radiation boundary conditions - Amster, Pablo Gustavo (2014)
Existence, uniqueness, and multiplicity properties are established via a variational formulation for a Painlevé II model subject to radiation boundary conditions in two-ion electrodiffusion. Numerical experiments using an adapted shooting method are also presented to support the theoretical results.